(untitled) (Revista de Ciências Agroveterinárias, 2019)
Because it is an unconventional vegetable, arrowroot is appropriate for family farming; there is a need to find alternative ways to make its growing more sustainable, however. The objective of this study was to evaluate the productive performance of rhizomes and starch of arrowroot ‘Seta’ intercropped with crotalaria. The experiment consisted of four treatments, corresponding to three harvest for crotalaria intercropped with arrowroot (90, 120 and 150 days after sowing) plus single cultivation of arrowroot. The experiment used a complete randomized block design with four replications. Mass production of crotalaria, macro and micronutrients contents in the cut material and infestation by invasive plants were evaluated at each harvest. At the harvest of arrowroot, productivity and format of rhizomes classes, macro and micronutrient contents were evaluated, and the export of nutrients and production of starch by rhizomes were estimated. The hasvests carried out at 120 and 150 DAS, despite propagating the highest values of weight and nutrients, provided lower yields of total, large rhizomes, and starch. Crotalaria hasvested at 90 DAS provided values higher than the cuts performed on 120 and 150 DAS for most evaluated variables, not differing from control, including starch. The intercropping provided less infestation by invasive plants. The intercropping between crotalaria and arrowroot provided is suitable as long as the harvest of this legume occurs up to 90 DAS.